Rancang Bangun Sistem Pembersih Kotoran Otomatis pada Kandang Kelinci Berbasis IoT (Internet Of Things) - Dedi Hermanto; Dodon Yendri (CHIPSET, 2022)
Rabbits have their charm for breeding because of the benefits they get from rabbits. However, rabbit farming has a fairly high challenge, namely rabbits die easily because of the cleanliness of the cage. The accumulation of rabbit droppings results in increased levels of ammonia gas which are harmful to rabbits, breeders, and even the environment. In cleaning the cage, rabbit breeders still use manual methods that are ineffective and inefficient. For this reason, a systemwas created to create an automatic feces cleaning system in the rabbit cage based on IoT (Internet of Things) by utilizing loadcell sensors to detect the weight of rabbit droppings that are accommodated on the conveyor belt. Belt conveyor as a medium that transports rabbit droppings. The MQ-135 sensor is used to detect the concentration of ammonia gas and the MCUESP8266 Node as a controller and IoT as a notification and as a system control via a smartphone. Based on testing of the system, the loadcell sensor as a measure of the weight of rabbit droppings has an accuracy rate of 97.43%. The MQ-135 sensor as a measure of theconcentration of ammonia gas in rabbit cages has an accuracy rate of 99.19%. The conveyor belt can move to dispose of rabbit droppings when the weight is > 1000 grams or the ammonia gas content is > 25 ppm. Then the Telegram application bot can 100% control the system by inputting commands and can receive notifications from the system. From testing the system as a whole, the system can work according to the desired function with a 100% success rate.